2005
DOI: 10.1111/j.0105-2896.2005.00274.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E and immune response in the aged: molecular mechanisms and clinical implications

Abstract: Nutritional status has been indicated as a contributing factor to age-related dysregulation of the immune response. Vitamin E, a lipid-soluble antioxidant vitamin, is important for normal function of the immune cells. The elderly are at a greater risk for vitamin E intake that is lower than recommended levels. Vitamin E supplementation above currently recommended levels has been shown to improve immune functions in the aged including delayed-type hypersensitivity skin response and antibody production in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
142
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(153 citation statements)
references
References 97 publications
(170 reference statements)
5
142
0
6
Order By: Relevance
“…41 Carotenoids also may influence the risk of NHL through immune-mediated pathways. 31,42 For example, elderly subjects who received supplementation with carotenoid-containing vitamins and trace elements showed a higher production of the cytokine IL-2 and a lower rate of infections, 43 and a carotenoid-rich vegetable intervention suppressed the secretion of IL-2 and IL-4. 44,45 This study had several strengths, including the prospective design that allowed for the prediagnostic assessment of serum carotenoid levels, the ethnic diversity of the study sample, and the population-based sampling frame allowing for generalizability of results.…”
Section: Discussionmentioning
confidence: 99%
“…41 Carotenoids also may influence the risk of NHL through immune-mediated pathways. 31,42 For example, elderly subjects who received supplementation with carotenoid-containing vitamins and trace elements showed a higher production of the cytokine IL-2 and a lower rate of infections, 43 and a carotenoid-rich vegetable intervention suppressed the secretion of IL-2 and IL-4. 44,45 This study had several strengths, including the prospective design that allowed for the prediagnostic assessment of serum carotenoid levels, the ethnic diversity of the study sample, and the population-based sampling frame allowing for generalizability of results.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E includes tocopherols and tocotrienols that exhibit the biological activity of α-tocopherol with both synthetic and natural forms of tocopherols being used experimentally. Results from animal studies have established that vitamin E can enhance T cell functions by directly influencing membrane integrity and signal transduction or, indirectly by reducing production of suppressive factors such as PGE 2 by macrophages (Meydani et al, 2005;Wu and Meydani, 2008). Many studies have reported beneficial effects of vitamin E supplementation in healthy elderly people (Belisle et al, 2008;De la Fuente et al, 2008;Meydani et al, 1990;Meydani et al, 1997;Pallast et al, 1999) with the majority finding improvements in immune function.…”
Section: Vitamin Ementioning
confidence: 99%
“…Micronutrients are known to have a wide range of effects on immune responses (8,9). The effect of vitamin A on measles vaccine responses has been studied in multiple clinical trials, but the results are unclear (10).…”
mentioning
confidence: 99%
“…Vitamin A may improve measles vaccine responses among boys when administered with the vaccine at 9 months of age but may worsen responses when administered at 6 months of age (10)(11)(12). Randomized controlled trials of vitamin E supplementation have found an improved innate immune activity, lymphocyte proliferation, and tetanus vaccine response among adults and elderly populations (9). Only one randomized trial of vitamin E supplementation and vaccine responses has been conducted in infants, and it reported no effect of supplementation on IgG titers following tetanus vaccination (13).…”
mentioning
confidence: 99%